Evaluation of color fading and bleeding of maroon polyester/cotton fabric using selected powder detergents - Tubilla, Hilza Joan Aleman; Escano, Maria Monica R. (2006.)
Color fading and staining due to bleeding of dyed fabrics are common problems encountered everyday as garments and other textile products are laundered at home. This study aimed to evaluate visually, through the American Association of Textile Chemists and Colorists (AATCC) Gray Scale for Color Change and AATCC Gray Scale for Staining, the effects of the three most commonly used powder detergent brands, based on one hundred (100) households surveyed in Pook Ricarte, UP Diliman, Quezon City, on color fading and bleeding of maroon polyester/cotton fabric. The research locale was in Philippine Textile Research Institute (PTRI) in Bicutan, Taguig. The experiment proper used procedure based on the standard method AATCC Test Method 61-1996: Colorfastness to Laundering, Home and Commercial: Accelerated (AATCC Technical Manual, Vol. 65 1990). The three most commonly used powder detergent brands that resulted in the survey were Surf: 88 votes, Ariel: 80 votes, and Tide: 78 votes. With these three brands, five varieties were utilized, which were Tide All-Purpose, Ariel Original Scent, Surf with Fabric Conditioner, Surf Gold with Active Scrub, and Surf Tawas. The general bases for these choices were the survey results and the availability of original formula variety of each brand. Since Surf has no original formula variety available, three of its many varieties were chosen randomly. The fabric used was commercially called "Tetoron" but fiber identification and composition test results indicated that the fabric was not 100% polyester rather 91.8% polyester and 8.2% cotton blends. The experiment had fifteen fabric samples prepared fr5om commercially bought maroon polyester/maroon fabric. Upon visual evaluation, of all the powder detergent varieties,Tide All-Purpose resulted top the least color fading as it registered only a Grade of 4.5, with Grade 5 having no color change, in the AATCC Gray Scale for Color Change as compared to the other four. In staining due to bleeding all of the powder detergent varieties failed in the test in all the six fibers comprised in the AATCC Multifiber |#10 for all of them registered grades other than Grade 5 (no staining) in the AATCC Gray Scale for Staining. The kind of dye applied to each of the polyester and cotton fiber in the blended maroon polyester/cotton fabric cannot be determined by the PTRI so the factor of the kind of dye as the reason of the evaluation results cannot be considered. Only the factors of inadequate dyeing preparation of polyester/cotton blend (Shore, 1998), inappropriate laundering temperature for polyester (Imada, 1999), or heat treatment after finishing for polyester (Imada, 1999) can be contemplated as the reasons for the evaluation results in the study.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Textile fibers, Synthetic; Detergents